Core Microbiota and Metabolome of Vitis vinifera L. cv. Corvina Grapes and Musts - Stefanini, Irene; Carlin, Silvia; Tocci, Noemi; Albanese, Davide; Donati, Claudio; Franceschi, Pietro; Paris, Michele; Zenato, Alberto; Tempesta, Silvano; Bronzato, Alberto; Vrhovsek, Urska; Mattivi, Fulvio; et al. (Frontiers in Microbiology, 2017)
The composition and changes of the fungal population and of the metabolites present in grapes and in ferments of Vitis vinifera L. cv. Corvina, one of the major components of the Amarone musts, were dissected aiming at the identification of constant characteristics possibly influenced by the productive process. The fungal populations and metabolomic profiles were analyzed in three different vintages. 454-pyrosequencing on the ribosomal ITS1 region has been used to identify the fungal population present in Corvina grapes and fresh must. Samples were also subjected to metabolomics analysis measuring both free volatile compounds and glycosylated aroma precursors through an untargeted approach with comprehensive two-dimensional gas chromatography time-of-flight mass spectrometry. Albeit strongly dependent on the climate, both the mycobiota and metabolome of Corvina grapes and fresh musts show some characteristics recursive in different vintages. Such persistent characteristics are likely determined by the method adopted to produce Amarone or other dry wines made from partially dried grapes. In particular, the harsh conditions imposed by the prolonged withering appear to contribute to the shaping of the fungal populations. The fungal genera and metabolites present in different vintages in Vitis vinifera L. cv. Corvina grapes and fresh musts represent core components of the peculiar technique of production of Amarone. Their identification allows the in-depth understanding and improved control of the process of production of this economically and culturally relevant wine.